Outcomes of HPV type-specific serostatus do not associate with oral or genital HPV-carriage in non-vaccinated women followed for three years - Salla Vuorinen; Kari Syrjänen; Tim Waterboer; Seija Grénman; Stina Syrjänen; Karolina Louvanto (BMC, 2022)
Abstract Background The role of human papillomavirus (HPV) antibodies acquired through natural infection and their role in protection for subsequent cervical or oral HPV-carriage remains unclear. Methods A total of 267 women, with a 36-months follow-up, from the Finnish Family HPV (FFHPV) study were evaluated to shed more light on persistent HPV-specific antibodies to genital or oral HPV-carriage, clearance or persistence during the three years follow-up. The type-specific seroprevalence for HPV genotypes 6, 11, 16, 18 and 45 in these women was assessed in relation to the detection of the same genotype or any HPV in their oral and genital samples. The following HPV serological outcomes where detected: being always seronegative, seroconversion or persistent seropositivity. Results Genital HPV16 infections were most prevalent at the end of the follow-up (24- and 36-month visit) among women who tested always seronegative for HPV16. No such associations between serology and HPV detection were established for the other HPV genotypes in the genital or oral samples. The development of long-term type-specific HPV 6,11,16,18 and 45 persistence (≥ 24 months) or clearance of the genital or oral infections was not different among the women with high HPV genotype specific antibody levels and those testing always HPV-seronegative. Conclusion No significant role was disclosed for the acquired natural high-level- or persistent HPV antibodies as determinants of the genital or oral HPV infection outcomes in these young, non-vaccinated women.